Evaluating sex offenders: a manual for civil commitments and beyond - Doren, Dennis M. (Sage Publications, 2002)
The relevant components of sex offender civil commitment laws -- Procedures for conducting the assessment -- Diagnostic issues within sex offender civil commitment assessments: defining relevant paraphilias -- Diagnostic issues within sex offender civil commitment assessments: diagnostic issues beyond the paraphilias -- Using risk assessment instrumentation -- Recidivism base rates -- Clinical adjustments -- The evaluation report and court testimony -- Ethical issues.